Comparative analysis of mesenchymal stem/stromal cells derived from human induced pluripotent stem cells and the cognate umbilical cord mesenchymal stem/stromal cells. Issue 1 (January 2023) - Wang, Quanlei; Wang, Yuwei; Chang, Chongfei; Ma, Feilong; Peng, Dongxiu; Yang, Shun; An, Yanru; Deng, Qiuting; Wang, Qixiao; Gao, Fei; Wang, Fei; Tang, Huiru; et al.
Abstract: Mesenchymal stem/stromal cells (MSCs) show tremendous potential for regenerative medicine due to their self-renewal, multi-differentiation and immunomodulatory capabilities. Largely studies had indicated conventional tissue-derived MSCs have considerable limited expandability and donor variability which hinders further application. Induced pluripotent stem cell (iPSCs)-derived MSCs (iMSCs) have created exciting source for standardized cellular therapy. However, the cellular and molecular differences between iMSCs and the cognate tissue-derived MSCs remains poorly explored. In this study, we first successfully reprogrammed human umbilical cords-derived mesenchymal stem/stromal cells (UMSCs) into iPSCs by using the cocktails of mRNA. Subsequently, iPSCs were further differentiated into iMSCs in xeno-free induction medium. Then, iMSCs were compared with the donor matched UMSCs by assessing proliferative state, differentiation capability, immunomodulatory potential through immunohistochemical analysis, flow cytometric analysis, transcriptome sequencing analysis, and combine with coculture with immune cell population. The results showed that iMSCs exhibited high expression of MSCs positive-makers CD73, CD90, CD105 and lack expression of negative-maker cocktails CD34, CD45, CD11b, CD19, HLA-DR; also successfully differentiated into osteocytes, chondrocytes and adipocytes. Further, the iMSCs were similar with their parental UMSCs in cell proliferative state detected by the CCK-8 assay, and in cell rejuvenation state assessed by β-Galactosidase staining and telomerase activity related mRNA and protein analysis. However, iMSCs exhibited similarity to resident MSCs in Homeobox (Hox) genes expression profile and presented better neural differentiation potential by activation of NESTIN related pathway. Moreover, iMSCs owned enhanced immunosuppression capacity through downregulation pools of pro-inflammatory factors, including IL6, IL1B etc. and upregulation anti-inflammatory factors NOS1, TGFB etc. signals. In summary, our study provides an attractive cell source for basic research and offers fundamental biological insight of iMSCs-based therapy.